(untitled) (NTU Journal of Agriculture and Veterinary Science, 2021)
The experiment was conducted in the autumn season (2019 AD) using the (RCBD) design and with three replications, in which the first factor tested the NPK nano fertilizer consisting of four levels (N4, N3, N2, N1) (0,75,150,225) PPM sequentially added twice the first with The seeds when planting. The second sprayed after a month of planting. The second factor uses different irrigation intervals consisting of three (F3, F2, F1) (8,6,4) days. The results of the experiment showed that the nano-fertilizer was significantly superior to Treatment N3 in all studied growth traits and yield, to give it the highest rate of traits: plant height, number of leaves, chlorophyll content, number of rows/horn, the weight of 500 grains, total dry matter yield, total grain yield per unit area, which amounted to (212.48 cm) and (14.04), (51.11), (13.51 row/cob), (136.83 g), (22.92 tons/ha) and (10.32 tons/ha) according to the order. As for the irrigation intervals, the irrigation interval was distinguished (every four days) and was significantly superior to the other irrigation intervals, except for the irrigation interval F2, which was distinguished in the height of the plant to give it the highest rate (203.95 cm). (234.14, 234.23) (15.13, 15.00), (55.31, 55.99), (14.13, 14.26 row/cob), (143.62, 143.62 g), (25.76, 25.63 tons/ha), (11.85, 11 .79 kg/ha) in order and without significant difference between them for the above traits.